2021
DOI: 10.3390/foods10040886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serving Plate Types and Color Cues on Liking and Purchase Intent of Cheese-Flavored Tortilla Chips

Abstract: Foods’ overall liking (OL) and purchase intent (PI) are influenced by visual inputs, such as color cues and serving plate types. Cheese-flavored tortilla chips (CFTC) from two formulations (A and B) with a noticeable color difference (∆E = 4.81) were placed on different serving plates (plastic, foam, and paper) and presented monadically to N = 83 consumers using a randomized/balanced block design in two sessions. Consumers evaluated likings of overall visual quality, color, crunchiness, saltiness, overall flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…ANOVA was also used to analyze instrumental color and texture measurements of fried catfish strips. JAR data were used to conduct penalty analysis [ 26 , 27 ] to determine the effects of non-JAR responses for crispiness on overall liking and liking of overall texture and crispiness. Logistic regression analysis (LRA) was used to identify significant predictors of PI, both before and after the BPI was given to consumers.…”
Section: Methodsmentioning
confidence: 99%
“…ANOVA was also used to analyze instrumental color and texture measurements of fried catfish strips. JAR data were used to conduct penalty analysis [ 26 , 27 ] to determine the effects of non-JAR responses for crispiness on overall liking and liking of overall texture and crispiness. Logistic regression analysis (LRA) was used to identify significant predictors of PI, both before and after the BPI was given to consumers.…”
Section: Methodsmentioning
confidence: 99%
“…These samples were similar in the a* and b*color dimensions (higher redness and lower yellowness compared to other treatments; Table 1 ). For all samples, mean ratings of OVQ (meant to encompass all aspects of product appearance [ 22 ]) were similar to those for color (all < 0.2 units apart on the 9-point scale; Table 2 ).…”
Section: Resultsmentioning
confidence: 90%
“…Consumer Study 1 ( N 1 = 115) collected hedonic information for a range of sensory attributes to identify the most acceptable treatments among Plain, LP, Paprika, and BBQ, beginning with the visual dimension, which is often the first used to evaluate product quality [ 22 ]. The most visually acceptable CSC treatment was that flavored with BBQ seasoning (liking of OVQ = 6.30, color liking = 6.47; Table 2 ), followed by Paprika-flavored treatment (liking of OVQ = 6.27, color liking = 6.25).…”
Section: Resultsmentioning
confidence: 99%
“…Predicting consumers' food choice with models based solely on hedonic information may not yield adequate prediction power compared to more holistic models that incorporate product-elicited emotions information [33]. In sensory studies, the collected data are usually analyzed via multivariate projection techniques such as principal component analysis, to describe the treatments and/or explain the observed differences among them [34]. However, predictive discriminant models can be built on sensory and emotional data to efficiently discriminate among treatments and to provide a measure of variable importance for future sensory analysis applications [35].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of product benefit claims, such as sustainability or high-nutritional value on the PI, emotions, and overall liking (OL) has been widely studied in different products. The effect of the claims varies depending on the food category, implied benefits, and the population being studied [34,37]. Several studies have reported the positive effects of disclosed benefit claims on consumer acceptability, perception, PI, or emotional profiles [38] albeit others have found them irrelevant [39] or not significant for certain demographic groups [40].…”
Section: Introductionmentioning
confidence: 99%